A Diagnosis of Russia’s Military Capability in a Situation of an Escalation of Hostility in Ukraine and Possible Implications for the Safety of the Eastern NATO Flank - Michalski, Daniel; Radomyski, Adam (Historia i Polityka, 2021)
The paper presents the results of research, whose main goal is to evaluate the aviation and rocket capability of the armed forces of the Russian Federation and Ukraine in terms of a possible launch of regular warfare. The authors primarily focus on changes in the military doctrine of the Russian Federation, which have created legal determinants of the use of armed forces outside the country’s territory in defense of national minorities, illustrated by taking control of Crimea. The authors also stress Russia’s military plans, including the development directions of the potential of armed forces as well as a possible threat to the security of the eastern NATO’s flank in the event of a conflict in Ukraine. In this respect, the capabilities of the air defense of countries on the eastern NATO flank, particularly Poland’s capability, were analyzed.